Factors Affecting Student Engagement in Universities of Kathmandu Valley - Shrestha, Aastha; Pradhan, Radhe Shyam (Nepalese Journal of Management, 2025)
This study examines the factors affecting student engagement in universities of Kathmandu valley. Student engagement is the dependable variable. The independent variables are curriculum design, extra-curricular activities, teaching methods, use of technology, class environment, student teacher relationship and absenteeism. The primary source of data is used to assess the opinions of the respondents regarding the factors affecting student engagement in universities of Kathmandu valley. The study is based on primary data of 240 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the different factors affecting student engagement in universities of Kathmandu valley. The result shows that curriculum design has a positive impact on student engagement indicating that curriculum design leads to increase student engagement in universities. Likewise, extracurricular activities have a positive impact on student engagement. It shows that extracurricular activities in universities increase the level of student engagement. Similarly, teaching methods has a positive impact on student engagement. It implies that better the methods of teaching, higher will be the engagement of student in universities. Further, use of technology has a positive impact on student engagement in universities. It indicates that use of technology increases the level of student engagement. Likewise, class environment has a positive impact on student engagement. It states that collaborative and respectful class environment leads to increase in the level of student engagement. Similarly, student teacher relationship has a positive impact on student engagement. It implies that positive student teacher relationship leads to increase in student engagement. Further, absenteeism has a negative impact on student engagement in universities. It indicates that less absenteeism increases the level of student engagement.